Investigation of CdSe Coatings for Solar Cell Application - Narayanan, Nivitha (Enhanced Knowledge in Sciences and Technology, 2022)
Cadmium Selenide (CdSe) quantum dots were synthesized using a solution-based method that was cost-effective and environmentally friendly. The synthesized quantum dots were subsequently spin-coated on glass substrates with a LAURELL WS-400-6NPPSS spin coater at varying coating speeds to form CdSe thin films. The optical characteristics of the thin films, such as absorbance and transmittance, were then studied using a Shimadzu UV-3600 plus (UVVIS Spectroscopy). Based on the absorbance spectrum and using the Tauc relation, the quantum dots were estimated to be in the size range of 2.9 nm. The transmittance spectrum shows a minimum of 50% transmittance which is in the range required for the CdSe thin films to be utilized as a window photovoltaic system. The results suggest that high transmittance may be achieved using spin coating, which is a low-cost process for producing thin coatings on window panes. Thermal and photostability tests were performed on the CdSe thin films after they were annealed at 150 °C for 4 hours. Another round of optical characterization was done after the stability tests to observe the physical durability of the quantum dots. However, the optical properties of the CdSe thin films were found to be affected. This might be attributed to the oxidation-induced degradation of the CdSe quantum dots. This can be further improved by further treatment of the coating or by coating the CdSe quantum dots with a shell.